STUDI KOMPARASI PENGGUNAAN MEDIA PAPERCRAFT DAN MEDIA GAMBAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SD - Naryla, Naryla; Margiati, K.Y.; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to determine the use of Papercraft Media and Picture Media to the students learning outcomes of mathematics of grader V SDN 36 Pontianak South. The research method used is quasi experimental method with non- equivalent control group design. The number of research subjects 59 students. Tool of data collection used is in the form of essay test ten questions. The result of this research is the average of post-test of experiment class 1 is 71,5 while eksperimen class 2 is 70,67. From result of t test, obtained tarithmeticequal to 0,2661 with ttable 1,62795 it means tarithmetic< ttable there was no significant effect between the papercraft media and picture media of learning outcomes to determine the nets of various simple space for students in the grader V SDN 36 Pontianak South. Â Keywords: Papercraft Media, Picture Media, Learning outcomes.